2010
DOI: 10.1590/s1414-81452010000100019
|View full text |Cite
|
Sign up to set email alerts
|

Conhecimento, atitude e práticas na prevenção do câncer de colo uterino e hpv em adolescentes

Abstract: O início sexual cada vez mais cedo propicia alta vulnerabilidade da adolescente a problemas da esfera sexual/reprodutiva, incluindo o câncer de colo uterino e a infecção pelo HPV. O presente estudo teve como objetivo identificar o conhecimento, atitude e prática na prevenção do câncer de colo uterino e infecção pelo HPV na população adolescente e avaliar as situações que as tornam vulneráveis. Trata-se de estudo transversal realizado em uma escola pública de São Paulo com 134 adolescentes entre 14 e 19 anos. V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
1
42

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 11 publications
2
15
1
42
Order By: Relevance
“…A study of 134 adolescents in the city of São Paulo showed that maternal schooling did not positively influence the cytopathological examination (p<0.001), even at the recommended periodicity (p<0,05). 12 This result differed from the present study, possibly due to the characteristics of the subjects participating in the two studies, especially in relation to the age group, once the lower the age is, the greater the degree of dependence of the subjects and consequently the shorter the years of studies completed.…”
Section: Discussioncontrasting
confidence: 96%
“…A study of 134 adolescents in the city of São Paulo showed that maternal schooling did not positively influence the cytopathological examination (p<0.001), even at the recommended periodicity (p<0,05). 12 This result differed from the present study, possibly due to the characteristics of the subjects participating in the two studies, especially in relation to the age group, once the lower the age is, the greater the degree of dependence of the subjects and consequently the shorter the years of studies completed.…”
Section: Discussioncontrasting
confidence: 96%
“…[19][20] A study conducted in ten schools in Rio de Janeiro, RJ, Brazil with 945 students aged from 13 to 21 years old, shows that, even though 94% of them recognize the protection conferred by condoms, only 34% reported their regular use. The study's authors associate this risky behavior with a low level of knowledge concerning STDs.…”
Section: Discussionmentioning
confidence: 99%
“…No Brasil, estima-se que ele seja a terceira neoplasia maligna mais comum entre as mulheres, sendo superado pelo câncer de pele (não melanoma) e pelo câncer de mama, e que seja a quarta causa de morte por câncer em mulheres 2 . Existe correlação entre a infecção do vírus HPV e a carcinogênese genital, levando à formação de lesões pré--neoplásicas 15 .…”
Section: Discussionunclassified
“…Foi questionado se o HPV está associado ao câncer de colo de útero. Em trabalho semelhante de Cirino et al 15 , foi encontrado que o conhecimento de prevenção do câncer de colo uterino e HPV foi maior nas adolescentes que já haviam iniciado suas atividades sexuais, quando comparadas com as que não haviam iniciado: 19,4% versus 32,6%. Como neste trabalho a grande maioria dos estudantes já tinha iniciado a atividade sexual, prova-se que os alunos conhecem a relação HPV e cân-cer de colo uterino 15 .…”
Section: Discussionunclassified